THE ECONOMIC BUBBLE AND ITS MEASUREMENT - GORGA, Carmine (Theoretical and Practical Research in Economic Fields, 2017)
In mainstream economics, the sight is restricted to forms of financial bubbles. In Concordian economics, rather than the behavior of the financial markets. instead, a bubble is defined as a separation of monetary values from values of real wealth. Hence, the concern is with the behavior of the entire economic system. Once defined, Concordian economics allows us to measure the bubble. To obtain this result, Concordian economics overcomes one of the major hurdles in economics, that is the measurement of real wealth as an entity separate and distinct from monetary wealth.